1979
DOI: 10.1246/bcsj.52.987
|View full text |Cite
|
Sign up to set email alerts
|

An UV-Visible Spectrophotometer Provided with a Photon Counting System for the Studies of Very Weak Absorption Spectra

Abstract: An ultrasensitive UV-visible spectrophotometer, of a single-beam type provided with a photon counting system having a time resolution of 10 ns has been constructed. It has been shown that absorption spectra can be measured to within an error of 10−5 in optical density with this instrument. Noise levels, measured as a function of the photon count numbers, are found to agree with the theoretically expected statistical fluctuation of the photons. Absorption spectra of thin naphthacene films, 32 nra or below in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Upon examining the vibrational spectra of several representative liquid hydrocarbons with various kinds of CH oscillators, Burberry et al suggested a “universal intensity concept”: for a given CH stretching overtone transition, a single absorption cross section per CH oscillator, regardless of type, could account for the observed spectral intensity at quantum levels v = 3, 4, 5, and 6 . However, overtone spectra of liquid cis - and trans -dichloroethylene measured by use of a photon-counting absorbance spectrophotometer , by Okada, Yamamoto, and Tsubomura showed results in contradiction to this concept . The integrated intensities of the cis isomer were greater than those of the trans isomer by a factor of 1.5−2.0.…”
Section: Introductionmentioning
confidence: 99%
“…Upon examining the vibrational spectra of several representative liquid hydrocarbons with various kinds of CH oscillators, Burberry et al suggested a “universal intensity concept”: for a given CH stretching overtone transition, a single absorption cross section per CH oscillator, regardless of type, could account for the observed spectral intensity at quantum levels v = 3, 4, 5, and 6 . However, overtone spectra of liquid cis - and trans -dichloroethylene measured by use of a photon-counting absorbance spectrophotometer , by Okada, Yamamoto, and Tsubomura showed results in contradiction to this concept . The integrated intensities of the cis isomer were greater than those of the trans isomer by a factor of 1.5−2.0.…”
Section: Introductionmentioning
confidence: 99%